Comparative study on ferrate oxidation of BPS and BPAF: Kinetics, reaction mechanism, and the improvement on their biodegradability. (1st January 2019) - Yang, Tao; Wang, Lu; Liu, Yulei; Huang, Zhuangsong; He, Haiyang; Wang, Xianshi; Jiang, Jin; Gao, Dawen; Ma, Jun
Abstract: Bisphenol S (BPS) and bisphenol AF (BPAF) were increasingly consumed and these compounds are resistant to environmental degradation. Herein, ferrate oxidation of BPS and BPAF was investigated, and biodegradability of the oxidation products was examined. The second-order reaction rate constants of ferrate with BPS and BPAF were 1.3 × 10 3  M −1 s −1 and 3 × 10 2  M −1 s −1, respectively, at pH 7.0, 25 °C. In the oxidation process, some BPS molecules dimerized, while other BPS molecules were oxidized through oxygen-transfer process, leading to the formation of hydroxylation products and benzene-ring cleavage products. The dominant reaction of BPAF with ferrate was oxygen-transfer process, and BPAF was degraded into lower molecular weight products. The variation of assimilable organic carbon (AOC) suggested that the biodegradability of BPAF and BPS was largely improved after ferrate oxidation. Compared with the BPS oxidation products, the BPAF oxidation products were easier to be bio-consumed. Pure culture test showed that BPAF inhibited the growth of Escherichia coli, while ferrate oxidation completely eliminated this toxic effect. Co-existing humic acid (HA, 1 mg C/L to 5 mg C/L) decreased the removal of BPS and BPAF with ferrate. Compared with BPAF, more oxidation intermediates formed in the ferrate oxidation of BPS may be reduced by HA to the parent molecular. Thus, the inhibition effect of HA on the ferrate oxidation of BPS was more obvious than that on BPAF. Graphical abstract: Highlights: Rate constants of Fe(VI) with BPS and BPAF were 1.3 × 10 3  M −1 s −1 and 3 × 10 2  M −1 s −1 (pH 7.0). BPAF was oxidized into small molecules by Fe(VI) through oxygen-transfer process. Biodegradability of BPAF and BPS was largely improved after ferrate oxidation. BPAF inhibited E. coli growth while no inhibition effects of BPS were observed. Ferrate oxidation removed inhibition effect of BPAF on E. coli growth.